Primer uporabe GIS-a v topoklimatski analizi pokrajine za potrebe vinogradništva (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1992)
For the needs of the analysis of the positions of viticulture areas and thechanges between the years 1824 and 1985 we have made a simple GIS for two example areas in the Middle Slovenske gorice. The DEM 50x50 m was used for GIS as a basic data layer. With the help of certain topoclimatical data we have tried to make a map of climatical conveniend areas for the vineyard. The changes of viticultural areas between the years 1824 and 1985 are shown as well.
Keywords: climate; geografija; geography; GIS; podnebje; vinogradništvo